2011
DOI: 10.2147/ijn.s21697
|View full text |Cite
|
Sign up to set email alerts
|

Nickel nanowires induced and reactive oxygen species mediated apoptosis in human pancreatic adenocarcinoma cells

Abstract: Background The ability to evade apoptosis is one of the key properties of cancer. The apoptogenic effect of nickel nanowires (Ni NWs) on cancer cell lines has never been adequately addressed. Due to the unique physicochemical characteristics of Ni NWs, we envision the development of a novel anticancer therapeutics specifically for pancreatic cancer. Thus, we investigated whether Ni NWs induce ROS-mediated apoptosis in human pancreatic adenocarcinoma (Panc-1) cells. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…They have also been shown to work as apoptotic agents for pancreatic cancer cells. 30 The large number of studies that use Ni NWs in comparison to Fe might suggest that Ni is a better candidate material despite its reported genotoxicity and cytotoxicity in Ni-containing dust particles. 31 Even though no work has been done that directly compares the cytotoxicity of Fe and Ni NWs under the same experimental conditions (cell line, incubation times, concentrations), a cross-comparison among studies 32,33 reveals that Fe NWs are considerably less toxic at a given concentration than are Ni NWs.…”
mentioning
confidence: 99%
“…They have also been shown to work as apoptotic agents for pancreatic cancer cells. 30 The large number of studies that use Ni NWs in comparison to Fe might suggest that Ni is a better candidate material despite its reported genotoxicity and cytotoxicity in Ni-containing dust particles. 31 Even though no work has been done that directly compares the cytotoxicity of Fe and Ni NWs under the same experimental conditions (cell line, incubation times, concentrations), a cross-comparison among studies 32,33 reveals that Fe NWs are considerably less toxic at a given concentration than are Ni NWs.…”
mentioning
confidence: 99%
“…2,10,28,35 This appearance is positively correlated with drug concentration and apoptosis induction despite the absence of normal caspase 3 in the cells. 23,24 It has been reported that wortmannin toxicity is more potent in DNA damaged cells than in nondamaged cells.…”
Section: Discussionmentioning
confidence: 98%
“…2 An ideal anticancer drug would inactivate cancer cells without much more effect in normal cells. 10 By inducing apoptosis specifically in cancer cells, this ultimate goal can be achievable. Phosphatidyl inositol 3-kinase (PI3K) helps cancer cells to avoid apoptosis and promotes cell cycle progression and proliferation as well as angiogenesis by modulating proapoptotic molecules, such as Bad and p53, [11][12][13][14][15] enabling cancer cells to grow in an uncontrolled manner.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that NPs of nickel ferrite (Ahamed et al 2011a, b) and nickel oxide (Ahamed et al 2013a, b) induced apoptosis in human lung adenocarcinoma (A549) and liver cancer (Hep G2) cells via bax/bcl-2 and caspase pathways stimulated by ROS. Nickel nanowires induced ROS-mediated apoptosis in human non-endocrine pancreatic (Panc-1) cancer cells (Hossain and Kleve 2011) and HeLa cells , thus showing potential for an innovative approach toward cancer therapy. Iron oxide (Fe3O4) NPs selectively induced apoptosis in cancer cells (HepG2 and A549) compared with two types of normal cells (human lung fibroblast IMR-90 and rat hepatocytes).…”
Section: Apoptotic Mode Of Cancer Cell Death By Metal-based Npsmentioning
confidence: 99%